"Being sexy" and the labor market: Self-objectification in job search related social networks. (April 2017) - Nistor, Nicolae; Stanciu, Ionuţ-Dorin
Abstract: When searching for jobs, many people resort to presenting themselves in ways construed to appeal the most to potential employers. Subsequently, they are prone to self-objectification (SO), a phenomenon studied so far in social psychology, but insufficiently in media psychology, and even less so in the context of job search through social networks. Whereas prior research shows mostly negative, i.e., dehumanizing SO effects, positive effects were also identified, e.g., reduced uncertainty and increased self-efficacy perceptions. The present correlational study proposes and validates a scale for job-search related SO, and applies this to verify a conceptual model of SO effects and predictors, based on a survey involving N = 258 social network users and structural equations modeling. A positive SO effect on job related self-efficacy and well-being was found. The study adds to social networks research, as well as to social psychological SO research, emphasizing positive SO effects. Implications for further research, practice and development are discussed. Highlights: Self-objectification has been insufficiently studied so far in work-related social networks. Self-objectification was previously known for its negative, i.e., dehumanizing effects. Self-objectification was best validated with an individual and a social component. Technology affordances had a positive influence on self-objectification. Self-objectification positively impacted Job-Related Self-Efficacy and well-being.